Peran Islamic Corporate Social Responsibility dalam Memoderasi Pengaruh Zakat Terhadap Kinerja Bank Umum Syariah - Sartini Wardiwiyono; Arty Fitria Jayanti (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2021)
The aim of this study is to investigate the role of Islamic Corporate Social Responsibility in moderating the effect of zakat on Islamic commercial banks’ financial performance. Out of 13 Islamic commercial bank listed by Otoritas Jasa Keuangan from 2012 to 2017, there were only five banks reporting Statement of Zakat Fund Sources and Disbursements. Hence, the final samples of this study consist of 30 observation data. Secondary data collected from 30 annual reports were gathered through documentation. This study utilizes moderated regression analysis to test three research hypotheses. The results shows several findings. Firstly, the amount of corporate zakat being reported in the Statement of Zakat Fund Sources and Disbursements has positive impact on Islamic banks’ financial performance. Secondly, Islamic CSR as measured by Islamic reporting index developed by Belal et al. (2015) has negative impact on Islamic Banks’ financial performance. Thirdly, the role of Islamic CSR in moderating the effect of zakat on financial performance was confirmed. Tujuan dari penelitian ini adalah untuk mengetahui peran Islamic Corporate Social Responsibility dalam memoderasi pengaruh zakat terhadap kinerja keuangan bank umum syariah. Dari 13 bank umum syariah yang terdaftar oleh Otoritas Jasa Keuangan dari tahun 2012 hingga 2017, hanya ada lima bank yang melaporkan Pernyataan Sumber dan Pencairan Dana Zakat. Sehingga sampel akhir dari penelitian ini terdiri dari 30 data observasi. Data sekunder yang dikumpulkan dari 30 laporan tahunan dikumpulkan melalui dokumentasi. Penelitian ini menggunakan analisis regresi yang dimoderasi untuk menguji tiga hipotesis penelitian. Hasilnya menunjukkan beberapa temuan. Pertama, jumlah zakat perusahaan yang dilaporkan dalam Laporan Sumber dan Pencairan Dana Zakat berdampak positif terhadap kinerja keuangan bank syariah. Kedua, CSR Islami yang diukur dengan indeks pelaporan Islam yang dikembangkan oleh Belal et al. (2015) berdampak negatif terhadap kinerja keuangan Bank Islam. Ketiga, peran CSR Islam dalam memoderasi pengaruh zakat terhadap kinerja keuangan dikonfirmasi.